Pengembangan instrumen skala general self-efficacy pada siswa sekolah menengah pertama - Athaya Yola Sevinka; Nyoman Dantes; Dewi Arum Widhayanti Metra Putri (Jurnal EDUCATIO: Jurnal Pendidikan Indonesia, 2023)
This research was conducted with the aim of producing a product in the form of a Self-efficacy Instrument for Grade VIII students of junior high schools in Kediri Regency. This study uses research with R&D research methods. The sampling technique uses a proportional stratified random sampling technique with a minimum sample of 175 students in 4 schools in the Kediri Regency, namely SMPN 1 Papar, SMPN 2 Papar, SMP Islam Kepung, SMPN 1 Gampengrejo. Then for the results of the CVR, a ΣCVR of 47.6 was obtained. And a CVI value of 0.95 which is categorized as "very high/relevant". Based on the broad empirical validity test in this development research involving a total of 175 students in testing the empirical validity level (main try out) using the SPSS program with the Pearson Correlation Product Moment test, it can be concluded that the 50 statement items on the self-efficacy scale have r count ( total correlation) > from 0.148 based on table r count with N = 175. So it can be interpreted that on the self-efficacy scale it has a valid or used status. Based on the reliability test, it showed that the reliability coefficient of the self-efficacy instrument obtained a result of 0.960. From this it can be concluded that this self-efficacy instrument has a very high level of interpretation. It can be concluded that this instrument is feasible to use and disseminate.